A polyester fiber production process without antimony metal catalysis
By using the titanium catalyst that uses the carrier load in the polyester fiber production process, the problem of high side reactions of titanium catalysts in the concentration reaction was solved, and high -efficiency and stable polyester preparation was realized, and the quality and application performance of the product were improved.
Patent Information
- Application Number
- CN202410690141.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-30
AI Technical Summary
Although the existing titanium-based catalysts have high catalytic activity in polycondensation reactions, they also promote the occurrence of side reactions, resulting in their stability and selectivity being inferior to those of antimony-based catalysts, limiting their application in the polyester industry.
By using porous silicon dioxide as a carrier, the surface of the surface is used to use tetharine gyamine, and reacts with acidic acid reactions. The load titanium activity center is prepared. Improve its decentralization and stability.
The titanium catalyst has significantly improved the response speed and yield during the preparation of polyester, reducing the reaction activation energy and time, and at the same time avoid the deficiency of the traditional titanium catalyst, which improves the hue and thermal stability of the polyester.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organosilicon materials, and in particular to a polyester fiber production process without antimony metal catalysis. Background Art
[0002] PET, the full name of polyethylene terephthalate, is widely used in different fields such as fiber, packaging, film and plastic due to its good performance, to replace aluminum, glass, ceramics, paper, wood, steel and other synthetic materials. Metal catalysts are basically used in the polycondensation and transesterification reactions of polyester synthesis. The metal in the catalyst provides an empty orbital, which coordinates with the lone pair of electrons in the carbonyl oxygen atom, increases the positive charge of the carbonyl carbon atom in the compound, and is conducive to the attack of the nucleophilic group. Antimony catalysts are generally used in the polyester polycondensation stage in the polyester process production, which has potential hazards to the environment and human health. Titanium catalysts are considered to be the most promising alternatives.
[0003] Titanium catalysts have much higher catalytic activity than antimony catalysts, and are non-toxic and pose no threat to human health. The catalytic principle of titanium catalysts in polycondensation reactions is slightly different from that of antimony catalysts. The titanium metal in the catalyst easily reacts with the terminal hydroxyl oxygen and the ester ether bond oxygen to form a five-membered ring structure. The coordination of this structure changes the charge density of each group, making the ester carbonyl carbon positively charged, making it easier for the nucleophilic reaction between the groups to proceed, thereby accelerating the speed of the polycondensation reaction. The central coordination mechanism in the process is relatively similar. Since this five-membered ring structure will reduce the bond order of the CO bond, it is easy to break. After this bond breaks, the main products of thermal degradation are acetaldehyde free radicals and terminal carboxyl groups. In addition, titanium catalysts can also promote interchain thermal degradation. Therefore, although titanium catalysts are highly active, they also promote thermal degradation reactions. It can be seen that while titanium catalysts promote polycondensation reactions, they also promote the occurrence of side reactions, resulting in their stability and selectivity being inferior to antimony catalysts. These shortcomings restrict the application and development of titanium catalysts in the polyester industry. Summary of the invention
[0004] The purpose of the present invention is to provide a polyester fiber production process without antimony metal catalysis to solve the following technical problems:
[0005] While existing titanium-based catalysts promote polycondensation reactions, they also promote the occurrence of side reactions, resulting in their stability and selectivity being inferior to antimony-based catalysts. These shortcomings restrict the application and development of titanium-based catalysts in the polyester industry.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A polyester fiber production process without antimony metal catalysis comprises the following steps:
[0008] S1: using terephthalic acid and ethylene glycol as raw materials to carry out an esterification reaction, and continuously adding a titanium catalyst during the esterification reaction to obtain an esterification product;
[0009] S2: inputting the esterification product into a pre-polycondensation kettle for pre-polycondensation reaction to obtain an oligomer;
[0010] S3: inputting the oligomer into a polycondensation kettle for polycondensation reaction to obtain a polycondensate;
[0011] S4: After the polycondensate is spun and post-finished, polyester fiber is obtained;
[0012] The preparation method of the titanium catalyst comprises the following steps:
[0013] A1: Add porous silica, tetraethylenepentamine and methanol into reactor A and disperse them evenly, stir at room temperature for 9-12 hours, filter and dry to obtain component 1;
[0014] A2: Add component 1, phytic acid and deionized water into reactor B, react at room temperature for 24-36 hours under stirring, centrifuge, wash and dry to obtain component 2;
[0015] A3: Add component 2, anhydrous ethanol component 1 and deionized water into reaction bottle A and disperse them evenly. Control the temperature at 25-35°C. Mix anhydrous ethanol component 2 and butyl titanate and add them into reaction bottle A. Keep the temperature for reaction for 12-24 hours. Centrifuge, wash and dry to obtain a titanium-based catalyst.
[0016] As a further solution of the present invention: the molar ratio of ethylene glycol to terephthalic acid is 1.1-1.3:1; the esterification reaction temperature is 225-245°C, the pressure is 45-65 kPa, and the reaction time is 3-6 hours.
[0017] As a further solution of the present invention: the temperature of the pre-polycondensation reaction is 260-270°C, the pressure is 1-15 kPa, and the reaction time is 0.5-1 h.
[0018] As a further embodiment of the present invention: the temperature of the polycondensation reaction is 270-280° C. and the pressure is 0.15-0.2 kPa.
[0019] As a further embodiment of the present invention: the polycondensation reaction is stopped when the viscosity of the polycondensate reaches 0.60-0.7 dL / g.
[0020] As a further embodiment of the present invention, the titanium content in the titanium-based catalyst is 6-20 ppm based on the total amount of terephthalic acid.
[0021] As a further solution of the present invention: the addition ratio of porous silica, tetraethylenepentamine and methanol in A1 is 1 g: 1-1.2 g: 10-20 mL.
[0022] As a further solution of the present invention: the mass ratio of component 1, phytic acid and deionized water in A2 is 1:1-1.5:10-100.
[0023] As a further solution of the present invention: the addition ratio of component 2, anhydrous ethanol component 1, deionized water, anhydrous ethanol component 2, and butyl titanate in A3 is 1g: 50-100mL: 10-20mL: 100-200mL: 3-6g.
[0024] Beneficial effects of the present invention:
[0025] The present application first uses porous silica as a carrier, uses tetraethylenepentamine to aminate its surface, and uses phytic acid to react with the amino groups on the surface of porous silica to obtain component two; finally, the titanium active center is loaded on a porous silica carrier with a large specific surface area to obtain a titanium-based catalyst with titanium as the central atom and a phosphorus compound as a ligand; through the role of the carrier, the present application can not only constrain the particle size of the catalyst, avoid the agglomeration of the active center, achieve good dispersibility, and improve the quality of the product; and introduce an inert center to reduce the local concentration of the active center on the catalyst surface, so that the active center achieves an ideal dispersion. The titanium-based catalyst prepared in the present application solves the problem that the activity of existing organic titanium compounds is difficult to regulate and the dispersibility is poor in high-viscosity reaction systems.
[0026] The titanium catalyst in this application has H + The metal ions act as catalysts, the positive charge of the carbonyl carbon attacks the hydroxyl oxygen in the ethylene glycol, and the titanium compound has a strong complexation with the reactants, which is more conducive to the coordination of the hydrogen ions on the terephthalic acid carboxylic acid with the lone pair of electrons of the carbonyl oxygen atom, increasing the positive charge of the carbonyl oxygen atom, thereby facilitating the carbonyl oxygen atom to combine with ethylene glycol to form BHET, and accelerating the esterification reaction. The titanium catalyst prepared in this application has a high catalytic activity for esterification, can greatly reduce the reaction activation energy and shorten the reaction time, and the addition of the catalyst can increase the reaction yield.
[0027] The titanium-based catalyst prepared in the present application has gotten rid of the defects of traditional titanium-based catalysts that are easily hydrolyzed to form TiO2, causing the polyester product to turn yellow, and have low thermal stability. The hue b and L value of the prepared polyester are improved. In addition, the titanium-based catalyst has high activity and a small amount of residual metal in the polyester, which is more conducive to spinning. DETAILED DESCRIPTION
[0028] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] The preparation method of the titanium catalyst comprises the following steps:
[0031] A1: 26 g of hexadecyltrimethylammonium bromide, 25 g of 1,3,5-triisopropylbenzene, 160 mL of ethanol, 640 mL of deionized water and 10 mL of 25 wt% ammonia water were added to a reaction kettle and dispersed evenly. The temperature was controlled at 50°C, 80 mL of tetraethyl orthosilicate was added, and the mixture was stirred for 3 h. The mixture was centrifuged, dried and calcined (the temperature was increased to 600°C at a heating rate of 2°C / min and calcined for 10 h) to obtain porous silica.
[0032] A2: Add 10 g of porous silica, 10 g of tetraethylenepentamine and 100 mL of methanol into reactor A and disperse them evenly. Stir at room temperature for 9 h, filter and dry to obtain component 1.
[0033] A3: Add 10g of component 1, 10g of phytic acid and 100mL of deionized water into reactor B, react at room temperature for 24h under stirring conditions, centrifuge, wash and dry to obtain component 2;
[0034] A4: Add 10g of component 2, 500mL of anhydrous ethanol component 1, and 100mL of deionized water into reaction bottle A and disperse them evenly. Control the temperature at 25°C. Mix 1000mL of anhydrous ethanol component 2 and 30g of butyl titanate and add them into reaction bottle A. Keep the temperature for 12h. Centrifuge, wash, and dry to obtain a titanium-based catalyst.
[0035] Example 2
[0036] The preparation method of the titanium catalyst comprises the following steps:
[0037] A1: 26 g of hexadecyltrimethylammonium bromide, 25 g of 1,3,5-triisopropylbenzene, 160 mL of ethanol, 640 mL of deionized water and 10 mL of 25 wt% ammonia water were added to a reaction kettle and dispersed evenly. The temperature was controlled at 50°C, 80 mL of tetraethyl orthosilicate was added, and the mixture was stirred for 3 h. The mixture was centrifuged, dried and calcined (the temperature was increased to 600°C at a heating rate of 2°C / min and calcined for 10 h) to obtain porous silica.
[0038] A2: 10 g of porous silica, 11 g of tetraethylenepentamine and 150 mL of methanol were added to reactor A and dispersed evenly, stirred at room temperature for 9 h, filtered and dried to obtain component 1;
[0039] A3: Add 10g of component 1, 13g of phytic acid and 500mL of deionized water into reactor B, react at room temperature for 24h under stirring conditions, centrifuge, wash and dry to obtain component 2;
[0040] A4: Add 10g of component 2, 500mL of anhydrous ethanol component 1, and 100mL of deionized water into reaction flask A and disperse them evenly. Control the temperature at 30°C. Mix 1500mL of anhydrous ethanol component 2 and 30g of butyl titanate and add them into reaction flask A. Keep the temperature for 16h. Centrifuge, wash, and dry to obtain a titanium-based catalyst.
[0041] Example 3
[0042] The preparation method of the titanium catalyst comprises the following steps:
[0043] A1: 26 g of hexadecyltrimethylammonium bromide, 25 g of 1,3,5-triisopropylbenzene, 160 mL of ethanol, 640 mL of deionized water and 10 mL of 25 wt% ammonia water were added to a reaction kettle and dispersed evenly. The temperature was controlled at 50°C, 80 mL of tetraethyl orthosilicate was added, and the mixture was stirred for 3 h. The mixture was centrifuged, dried and calcined (the temperature was increased to 600°C at a heating rate of 2°C / min and calcined for 10 h) to obtain porous silica.
[0044] A2: Add 10 g of porous silica, 12 g of tetraethylenepentamine and 200 mL of methanol into reactor A and disperse them evenly. Stir at room temperature for 12 h, filter and dry to obtain component 1.
[0045] A3: Add 10g of component 1, 15g of phytic acid and 1000mL of deionized water into reactor B, react at room temperature for 36h under stirring conditions, centrifuge, wash and dry to obtain component 2;
[0046] A4: Add 10g of component 2, 1000mL of anhydrous ethanol component 1, and 200mL of deionized water into reaction flask A and disperse them evenly. Control the temperature at 35°C. Mix 2000mL of anhydrous ethanol component 2 and 30g of butyl titanate and add them into reaction flask A. Keep the temperature for reaction for 24h. Centrifuge, wash, and dry to obtain a titanium-based catalyst.
[0047] Example 4
[0048] A polyester fiber production process without antimony metal catalysis comprises the following steps:
[0049] S1: Ethylene glycol and terephthalic acid in a molar ratio of 1.3:1 are used as raw materials for esterification reaction, the esterification reaction temperature is 225°C, the pressure is 65 kPa, and the reaction time is 6 hours. During the esterification reaction, the titanium catalyst prepared in Example 1 is continuously added, and the titanium content in the titanium catalyst accounts for 10 ppm of the total amount of terephthalic acid, to obtain an esterification product;
[0050] S2: The esterification product is input into a pre-polycondensation kettle for pre-polycondensation reaction, the pre-polycondensation reaction temperature is 265°C, the pressure is 15 kPa, and the reaction time is 0.5 h to obtain a polymer;
[0051] S3: feeding the oligomer into a polycondensation kettle for polycondensation reaction at a temperature of 280° C. and a pressure of 0.15 kPa. The reaction is stopped when the viscosity of the polycondensation product reaches 0.67 dL / g to obtain a polycondensation product;
[0052] S4: The condensation polymer at 280°C enters the spinning box and is extruded through the micropores of the spinneret. The melt stream is quenched by an annular air flow facility. The temperature of the quenching air is 30°C. The filaments are then led to the winding roller by the traction roller and sent to the horizontally movable wire drum by the feeding wheel. The traction speed and winding speed are controlled at 1000m / min.
[0053] Post-processing: the filament bundles drawn out from the filament drum are formed into filament sheets, and the speed difference of the filament sheets is formed by the first stretching machine and the second stretching machine to realize mechanical stretching of the filament sheets, the first stretching ratio is 3.2, and the stretching medium is a 55°C water bath; the speed difference of the filament sheets is formed by the third stretching machine and the second stretching machine to form a second stretching of the filament sheets, the second stretching ratio is 1.1, and the stretching medium is 130°C steam; the filament sheets after stretching are heat-set in a tension heat-setting roller facility, and the heat-setting temperature is 200°C; after cooling, the surface of the filament sheets is oiled, and through a tension regulator and steam heating, the filament sheets enter a crimping machine for mechanical crimping, and the temperature of the mechanical crimping is 100°C; then the filament sheets are relaxed and set in a tension-free heat-setting machine at a temperature of 90°C; finally, the filament sheets are introduced into a cutting machine to cut the filament sheets into polyester staple fibers.
[0054] Example 5
[0055] Compared with Example 4, Example 5 is only that the titanium-based catalyst prepared in Example 1 added in Example 4 is replaced by an equal amount of the titanium-based catalyst prepared in Example 2, and the other components and preparation methods are exactly the same as those in Example 4.
[0056] Example 6
[0057] Compared with Example 4, Example 6 is only that the titanium-based catalyst prepared in Example 1 added in Example 4 is replaced by an equal amount of the titanium-based catalyst prepared in Example 3, and the remaining components and preparation method are exactly the same as those in Example 4.
[0058] Comparative Example 1
[0059] The preparation method of the titanium catalyst comprises the following steps:
[0060] A1: 26 g of hexadecyltrimethylammonium bromide, 25 g of 1,3,5-triisopropylbenzene, 160 mL of ethanol, 640 mL of deionized water and 10 mL of 25 wt% ammonia water were added to a reaction kettle and dispersed evenly. The temperature was controlled at 50°C, 80 mL of tetraethyl orthosilicate was added, and the mixture was stirred for 3 h. The mixture was centrifuged, dried and calcined (the temperature was increased to 600°C at a heating rate of 2°C / min and calcined for 10 h) to obtain porous silica.
[0061] A2: Add 10g of component 1, 13g of phytic acid and 500mL of deionized water into reactor B, react at room temperature for 24h under stirring conditions, centrifuge, wash and dry to obtain component 2;
[0062] A3: Add 10g of component 2, 500mL of anhydrous ethanol component 1 and 100mL of deionized water into reaction bottle A and disperse them evenly. Control the temperature at 30°C. Mix 1500mL of anhydrous ethanol component 2 and 30g of butyl titanate and add them into reaction bottle A. Keep the temperature for 16h. Centrifuge, wash and dry to obtain a titanium-based catalyst.
[0063] Comparative Example 2
[0064] The preparation method of the titanium catalyst comprises the following steps:
[0065] A1: 26 g of hexadecyltrimethylammonium bromide, 25 g of 1,3,5-triisopropylbenzene, 160 mL of ethanol, 640 mL of deionized water and 10 mL of 25 wt% ammonia water were added to a reaction kettle and dispersed evenly. The temperature was controlled at 50°C, 80 mL of tetraethyl orthosilicate was added, and the mixture was stirred for 3 h. The mixture was centrifuged, dried and calcined (the temperature was increased to 600°C at a heating rate of 2°C / min and calcined for 10 h) to obtain porous silica.
[0066] A2: 10 g of porous silica, 11 g of tetraethylenepentamine and 150 mL of methanol were added to reactor A and dispersed evenly, stirred at room temperature for 9 h, filtered and dried to obtain component 1;
[0067] A3: Add 10g of component 2, 500mL of anhydrous ethanol component 1 and 100mL of deionized water into reaction bottle A and disperse them evenly. Control the temperature at 30°C. Mix 1500mL of anhydrous ethanol component 2 and 30g of butyl titanate and add them into reaction bottle A. Keep the temperature for 16h. Centrifuge, wash and dry to obtain a titanium-based catalyst.
[0068] Comparative Example 3
[0069] The preparation method of the titanium catalyst comprises the following steps:
[0070] A1: 26 g of hexadecyltrimethylammonium bromide, 25 g of 1,3,5-triisopropylbenzene, 160 mL of ethanol, 640 mL of deionized water and 10 mL of 25 wt% ammonia water were added to a reaction kettle and dispersed evenly. The temperature was controlled at 50°C, 80 mL of tetraethyl orthosilicate was added, and the mixture was stirred for 3 h. The mixture was centrifuged, dried and calcined (the temperature was increased to 600°C at a heating rate of 2°C / min and calcined for 10 h) to obtain porous silica.
[0071] A2: Add 10g of porous silica, 500mL of anhydrous ethanol component 1, and 100mL of deionized water into reaction bottle A and disperse them evenly. Control the temperature at 30°C. Mix 1500mL of anhydrous ethanol component 2 and 30g of butyl titanate and add them into reaction bottle A. Keep the temperature for 16h. Centrifuge, wash, and dry to obtain a titanium-based catalyst.
[0072] Comparative Example 4
[0073] Compared with Example 4, Comparative Example 4 is that only the titanium-based catalyst prepared in Example 1 added in Example 4 is replaced by an equal amount of the titanium-based catalyst prepared in Comparative Example 1, and the remaining components and preparation method are completely consistent with Example 4.
[0074] Comparative Example 5
[0075] Compared with Example 4, Comparative Example 5 is that only the titanium-based catalyst prepared in Example 1 added in Example 4 is replaced by an equal amount of the titanium-based catalyst prepared in Comparative Example 2, and the remaining components and preparation method are completely consistent with Example 4.
[0076] Comparative Example 6
[0077] Compared with Example 4, Comparative Example 6 is the case in which only the titanium-based catalyst prepared in Example 1 added in Example 4 is replaced by an equal amount of the titanium-based catalyst prepared in Comparative Example 3, and the remaining components and preparation method are completely the same as those in Example 4.
[0078] Comparative Example 7
[0079] Compared with Example 4, Comparative Example 4 only replaces the titanium-based catalyst prepared in Example 1 added in Example 4 with an equal amount of ethylene glycol antimony, in which the antimony content of ethylene glycol antimony accounts for 200 ppm of the total amount of terephthalic acid, and the remaining components and preparation method are exactly the same as those of Example 4.
[0080] Performance Testing
[0081] (1) Esterification rate of esterification reaction: The components of the distillate samples at each time point of the esterification reaction were analyzed by gas chromatography, and the contents of water and ethylene glycol in the distillate at each time point were calculated. The esterification rate (E) was calculated using the following formula:
[0082] E= N / 2No
[0083] Where No is the initial number of moles of terephthalic acid added to the reactor; Nw is the number of moles of water in the distillate; and the reaction time T is recorded when the esterification rate reaches 90%. E90 ; The test results are shown in Table 1;
[0084] (2) Determination of hue of polyester products: Use a standard light source to illuminate the polyester sample, and then pass the light passing through the sample through two photoelectric tubes equipped with blue and green filters respectively. The measured hue will be displayed in digital form on an instrument equipped with a colorimeter, which are L value and b value respectively. The L value represents the whiteness of the polyester, and the b value represents the yellowness index of the polyester. The test results are shown in Table 1;
[0085] Table 1: Statistical table of performance test data of Examples 4-6 and Comparative Examples 4-7
[0086] Esterification rate / % <![CDATA[T E90 / min]]> L value b-value Example 4 91.5 79 88.7 1.6 Example 5 92.1 78 89.9 1.5 Example 6 91.2 82 88.2 2.0 Comparative Example 4 89.1 88 85.3 3.2 Comparative Example 5 87.8 89 82.2 3.4 Comparative Example 6 86.9 92 81.4 3.9 Comparative Example 7 92.2 103 87.9 1.3
[0087] As can be seen from Table 1, the titanium-based catalyst prepared in the present application is used in the polyester preparation process, which not only accelerates the reaction rate of polyester, but also gets rid of the defects of traditional titanium-based catalysts that are easily hydrolyzed to form TiO2, making the polyester product yellow, and having low thermal stability.
[0088] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A polyester fiber production process without antimony metal catalysis, characterized in that: The steps include: S1: using terephthalic acid and ethylene glycol as raw materials to carry out an esterification reaction, and continuously adding a titanium catalyst during the esterification reaction to obtain an esterification product; S2: inputting the esterification product into a pre-polycondensation kettle for pre-polycondensation reaction to obtain an oligomer; S3: inputting the oligomer into a polycondensation kettle for polycondensation reaction to obtain a polycondensate; S4: After the polycondensate is spun and post-finished, polyester fiber is obtained; The preparation method of the titanium-based catalyst comprises the following steps: A1: Add porous silica, tetraethylenepentamine and methanol into reactor A and disperse them evenly, stir at room temperature for 9-12 hours, filter and dry to obtain component 1; A2: Add component 1, phytic acid and deionized water into reactor B, react at room temperature for 24-36 hours under stirring, centrifuge, wash and dry to obtain component 2; A3: Add component 2, anhydrous ethanol component 1 and deionized water into reaction bottle A and disperse them evenly. Control the temperature at 25-35°C. Mix anhydrous ethanol component 2 and butyl titanate and add them into reaction bottle A. Keep the temperature for reaction for 12-24 hours. Centrifuge, wash and dry to obtain a titanium-based catalyst.
2. The process for producing polyester fiber without antimony metal catalysis according to claim 1, characterized in that: The molar ratio of ethylene glycol to terephthalic acid is 1.1-1.3:1; the esterification reaction temperature is 225-245°C, the pressure is 45-65kPa, and the reaction time is 3-6h.
3. The process for producing polyester fiber without antimony metal catalysis according to claim 1, characterized in that: The temperature of the pre-polycondensation reaction is 260-270°C, the pressure is 1-15 kPa, and the reaction time is 0.5-1 h.
4. The process for producing polyester fiber without antimony metal catalysis according to claim 1, characterized in that: The temperature of the polycondensation reaction is 270-280°C and the pressure is 0.15-0.2 kPa.
5. The process for producing polyester fiber without antimony metal catalysis according to claim 1, characterized in that: The polycondensation reaction was stopped when the viscosity of the polycondensate reached 0.60-0.7 dL / g.
6. The process for producing polyester fiber without antimony metal catalysis according to claim 1, characterized in that: The titanium content in the titanium catalyst accounts for 6-20 ppm of the total amount of terephthalic acid.
7. The process for producing polyester fiber without antimony metal catalysis according to claim 1, characterized in that: The addition ratio of porous silica, tetraethylenepentamine and methanol in A1 is 1 g: 1-1.2 g: 10-20 mL.
8. The process for producing polyester fiber without antimony metal catalysis according to claim 1, characterized in that: The mass ratio of component 1, phytic acid and deionized water in A2 is 1:1-1.5:10-100.
9. The process for producing polyester fiber without antimony metal catalysis according to claim 1, characterized in that: The addition ratio of component 2, anhydrous ethanol component 1, deionized water, anhydrous ethanol component 2, and butyl titanate in A3 is 1g: 50-100mL: 10-20mL: 100-200mL: 3-6g.
Citation Information
Patent Citations
Method for manufacturing directly-spun PET (polyethylene glycol terephthalate) polyester staple fibers by aid of titanium catalysts
CN105970342A
Preparation method and application of green titanium polyester catalyst
CN110606946A